Impact of "El Niño 1997-98" on larval settlement of some benthic marine invertebrates of Independencia Bay, Pisco-Peru - Ramos, Elmer (1999)
The changes and magnitude of "El Niño" (EN) impact, on larval settlement mechanisms, of some benthic marine invertebrates, on artificial filamentous substrates (nylon fiber) were monthly evaluated, from January 1996 to July 1998, in a 10m depth station located eastern of Independencia Island in Independencia Bay. During 1996, in "La Niña" (LN) warm phase, the number of species showed a peak in April and the density showed one in June, The total density and species number showed a firsl peak in March 1997, then, a second peak in February and July 1998 in the warm phase EN 1997-98, respectively. The bivalve Hiatella solida, turbellaria Notoplana sp., and gastropod Caecum chilense constituted a first group of species that intensified its settlement during cold phase LN 1996. The second group intensified its settlement in earlier warm phase of EN 1997-98, and it was confirmed by the brachiopod Discinisca lamel/osa, echinoderm Ophiactís kroyeri, and the bivalves of Mytilidae family. At the beginning of 1998, a third group showed an intensification of larval settlement in later phase of the EN 1997-98 warm phase, and it was formed by the bivalve Argopecten purpuratus, and a turriform gastropod. The appearance of recently settlement larvae of tropical species as the bivalve Pteria stema, and the gastropod Epitonium sp. appeared in later warm phase of ENSO 1997-98.